Design, analysis and fabrication of Fractal Antenna for multiband application - Saidatul Norlyana Azemi (Universiti Malaysia Perlis, 2008)
A fractal is a recursively generated object having a fractional dimension. Many objects, including antennas, can be designed using the recursive nature of a fractal. There is a various type of fractal antenna. In this project, have two type of fractal antenna, which are Hexagonal Fractal Loop Antenna and Sierpinski Carpet Square Fractal Antenna. Both of these antennas will be designing using ADS Software (Advanced Design Technologies) by Agilent Technologies. This work is an attempt to model, simulate and fabricate two types of microstrip fractal antenna for multi band applications. Simulations are done using Advanced Design Technologies software. The ADS simulated results are compared with its corresponding measurements of fabricated hardware. Fabrication of antenna is done using wet-etching method, on FR-4 dielectric. The unique properties of fractals have been exploited in order to develop a new class of antenna-element designs that are multi-band and or compact in size.